2016
DOI: 10.1111/jfb.13034
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian differentiation and development in cachara Pseudoplatystoma fasciatum

Abstract: One thousand five hundred cachara or tiger shovelnose catfish Pseudoplatystoma fasciatum, obtained from induced reproduction, were used to determine the onset of ovarian differentiation and development and to record the main characteristics of this process. Samples were collected from 0 to 240 days post-fertilization (dpf) and the results classified into stages I-XII. Ovarian formation was histologically detected for the first time when juveniles measured mean ± s.d. 51·5 ± 8·3 mm total length (LT ) at 39-45 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Moreover, with the management conditions applied in this study, we observed a relatively late gonadal differentiation process in pacu (♀: 150 days, 18.21 ± 1.22 g and mean length of 9.55 ± 0.65 cm) compared with other tropical species used in aquaculture, such as cachara, Pseudoplatystoma fasciatum (♀ and ♂: 39–45 days; 51.5 cm and 0.66 g) (Valentin et al, 2016), lambari, Astyanax altiparanae , (♀: 58 days and ♂: 73 days) (Adolfi et al, 2015) and tambaqui, Colossoma macropomum (♀ 4.0 cm) (Lobo et al, 2020). In this concern, we must also consider that the growth rates obtained in the present study were far below the growth rates reported for other pacu growth‐out phase studies.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, with the management conditions applied in this study, we observed a relatively late gonadal differentiation process in pacu (♀: 150 days, 18.21 ± 1.22 g and mean length of 9.55 ± 0.65 cm) compared with other tropical species used in aquaculture, such as cachara, Pseudoplatystoma fasciatum (♀ and ♂: 39–45 days; 51.5 cm and 0.66 g) (Valentin et al, 2016), lambari, Astyanax altiparanae , (♀: 58 days and ♂: 73 days) (Adolfi et al, 2015) and tambaqui, Colossoma macropomum (♀ 4.0 cm) (Lobo et al, 2020). In this concern, we must also consider that the growth rates obtained in the present study were far below the growth rates reported for other pacu growth‐out phase studies.…”
Section: Discussionmentioning
confidence: 57%
“…compared with other tropical species used in aquaculture, such as cachara, Pseudoplatystoma fasciatum (♀ and ♂: 39-45 days; 51.5 cm and 0.66 g) (Valentin et al, 2016), lambari, Astyanax altiparanae, (♀:…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of the testis was possible due to the future fringes appearance of the gonad as a result of the proliferation of the stroma and also the early cellular arrangement (circular formation) of somatic cells in the distal region; which later originated the sperm ducts in P. fasciatum and which has been reported in several gonochoristic species (Kobayashi et al, 2011;Komatsu, Nakamura, & Nakamura, 2006;Meijide, Lo Nostro, & Guerrero, 2005). Therefore, the morphological indications of gonadal differentiation may be related to the different arrangements of somatic and germ cells during early development (Mazzoni, Grier, & Quagio-Grassiotto, 2010, 2014Valentin et al, 2016), and may precede the formation of sperm ducts in males and the start of meiosis in females (Kobayashi et al, 2011;.…”
Section: Discussionmentioning
confidence: 95%
“…It alters gonad morphology and affects growth rate and maturation age (Strussmann, Cota, Cota, Phonlor, Higuchi, & Takashima, 1996;Strussmann, Takashima, Takashima, & Toda, 1996); which are characteristics of commercial interest, especially in monosex farming (Marjani, Jamili, & Mostafavi, 2009). Therefore, the morphological indications of gonadal differentiation may be related to the different arrangements of somatic and germ cells during early development (Mazzoni, Grier, & Quagio-Grassiotto, 2010, 2014Valentin et al, 2016), and may precede the formation of sperm ducts in males and the start of meiosis in females (Kobayashi et al, 2011;. Early identification of the testis was possible due to the future fringes appearance of the gonad as a result of the proliferation of the stroma and also the early cellular arrangement (circular formation) of somatic cells in the distal region; which later originated the sperm ducts in P. fasciatum and which has been reported in several gonochoristic species (Kobayashi et al, 2011;Komatsu, Nakamura, & Nakamura, 2006;Meijide, Lo Nostro, & Guerrero, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of gonadal sex differentiation is important for the artificial sex reversal induction (Valentin et al., ; Zhao et al., ). Sex reversal in most teleost fish is induced during or before the period of gonadal sex differentiation, which is plastic in fish and thought to be controlled by genetic and environmental factors (Lou et al., ; Nakamura, Kobayashi, Chang & Nagahama, ).…”
mentioning
confidence: 99%